THE ROLE OF DEDOLLARIZATION AND BRICS EXPANSION IN STRENGTHENING ECONOMIC RESILIENCE IN DEVELOPING COUNTRIES: (A Study of Brazil, Russia, India, Indonesia, and Egypt) - Muhamad David; Erni Achmad; Putri Intan Suri (Yayasan Nuraini Ibrahim Mandiri, 2026)
The dominance of the United States dollar in the global financial system has persisted for decades and has influenced the economic stability of developing countries. Dependence on the dollar makes developing countries vulnerable to exchange rate fluctuations, United States monetary policy, and global economic pressures. Therefore, the phenomenon of dedollarization has emerged as an effort to reduce dependence on the dollar through the use of local currencies in international trade and the diversification of foreign exchange reserves. In this context, the BRICS group plays an important role in promoting the dedollarization agenda and expanding economic cooperation among developing countries. This study aims to analyze the development of dedollarization and the expansion of BRICS in strengthening the economic resilience of developing countries, particularly Brazil, Russia, India, Indonesia, and Egypt. The research method employed is a qualitative descriptive approach using secondary data in the form of foreign exchange reserves, Gross Domestic Product (GDP), exchange rates, and international trade indicators during the 2015-2024 period. Data were obtained from various official sources such as the International Monetary Fund, the World Bank, and publications from the central banks of each country. The results indicate that dedollarization policies and the expansion of BRICS contribute to strengthening the economic resilience of developing countries through increased foreign exchange reserves, diversification of international trade, and stronger regional economic cooperation. Russia and India demonstrate relatively stronger economic resilience due to their large foreign exchange reserves and substantial economic capacity. Meanwhile, Indonesia and Egypt still face various structural challenges in improving economic stability and global trade capacity.